El concepto de corrupción. Su evolución hacia un nuevo delito de fraude en el deporte como forma de corrupción en el sector privado - Caruso Fontán, María Viviana (FORO. Revista de Ciencias Jurídicas y Sociales, Nueva Época, 2009)
The phenomenon of corruption is characterised by the following elements: the violation of a duty of status, a benchmark regulatory system and the expectation of obtaining an undue gain. This phenomenon was traditionally associated with the public sphere. In recent years this presumption has been modified, especially due to the influence of diverse international bodies. The consequence of this circumstance has been the incorporation of an offence of corruption in the private sector into the Bill on the reform of the criminal code, so as to penalise acts of corruption in commercial transactions. Despite this incorporation, the issue is especially polemical, since it has been proposed that this be extended to cover fraudulent conduct in sport.